The Impact of SAVI Learning Model on Students' Speaking Skills for Elementary Levels - Andi Hamsiah; Asdar Asdar; St. Haliah Batau (STAI Hubbulwathan Duri, 2023)
The field of education in modern times has advanced quickly. Learning is made easier by educators and school infrastructure. Every student's potential is still being maximized through ongoing design improvements in the teaching and learning process. This research investigates the effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) model on the students' speaking skills. The research employs true experimental with a pretest-posttest control group design, which gives a test before and after the treatment using the SAVI model. The sample of this study is two classes, namely class VA as the experimental class, totaling 30 students, and class VB as the control class, totaling 34 students. The data collection techniques used in this study are observation, test, and documentation, which are analyzed with descriptive statistics. The data is analyzed using the inferential test formula (t-test). The results showed that the SAVI model was effectively used in learning students' speaking skills. It can be seen from the results of the hypothesis, namely the value of t_count 2.47 and 2.00 so that the results are accepted and rejected. Thus, it can be concluded that there is a positive impact of the SAVI learning model on students' speaking skills. The teacher can apply this model in teaching the students whose grades are below the class average so that this method can be used in learning students' speaking skills in Indonesian subjects.